Pengaruh Media Crossword Puzzle terhadap Penguasaan Goi Siswa Kelas XI SMAN 1 X Koto - Putri, Serly Deliza; Wikarya, Rahmi Oktayory (AHKAM, 2024)
When learning Japanese language, vocabulary is one of the most important elements that students must understand and master. In reality, there are several problems faced by students when learning vocabulary. Based on interviews with the relevant teacher, it was shown that many students have difficulty mastering vocabulary. This is due to the large number of vocabulary words that must be memorized in each chapter of the learning material. Therefore, more varied teaching methods and media are needed to help students understand vocabulary more easily. By using crossword puzzle media can resolved this problem. The purpose of this study is to describe the level of influence of crossword puzzle media on the vocabulary mastery of 11th-grade students. This research is quantitative research with a pre-experimental design of the one-group pre-test post-test design type. Data was collected using a purposive sampling technique, specifically class XI.F.4, which consists of 34 students. Based on the results of the t-test, it was concluded that H1 was accepted at a significance level of 0.05 because the sig value < 0.05 (0.000 < 0.05), which means that the vocabulary mastery in the post-test is significantly different from the pre-test. In other words, the use of crossword puzzle media is effective in vocabulary learning.